Le projet Disraeli : idéaux et limites de la collaboration en photographie - Tousignant, Zoë (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2024)
This article revisits the Disraeli project, a collective documentary portrait of the rural town of Disraeli, Quebec, undertaken in 1972 by photographers Claire Beaugrand-Champagne, Michel Campeau, Roger Charbonneau and Cedric Pearson, and researchers Ginette Laurin and Maryse Pellerin. Immediately following its initial dissemination, the project—now considered a pivotal event in the history of photography in Quebec—sparked a veritable media storm, the first to be centered on the ethics of photographic representation. The article reconsiders the emergence, realization, and reception of this collective work with a focus on collaboration, a key notion for several recent studies on photography. It argues that in order for the Disraeli project to be seen as a successful act of collaboration between the photographers and the people photographed, this notion must expand to allow controversy and disagreement to be part of the story told.